Meso-Phenyltetrabenzotriazaporphyrin based double-decker lanthanide(iii) complexes: synthesis, structure, spectral properties and electrochemistry1. Issue 37 (7th October 2015) - Pushkarev, Victor E.; Kalashnikov, Valery V.; Tolbin, Alexander Yu.; Trashin, Stanislav A.; Borisova, Nataliya E.; Simonov, Sergey V.; Rybakov, Victor B.; Tomilova, Larisa G.; Zefirov, Nikolay S.
<x xml:space="preserve">Abstract</x> A series of tetrabenzotriazaporphyrin half-sandwich and sandwich compounds, including unexpected meso-dearylated derivatives as well as the first triple-decker, have been prepared.